Attitudes and knowledge of nursing technicians about care to patients with mental disorders - Zilda Maria de Melo; Natália Priolli Jora Pegoraro; Manoel Antônio dos Santos; Sandra Cristina Pillon (Universidade Federal de Goias, 2016)
The study aimed to evaluate attitudes and theoretical and practical knowledge of nursing technicians about the care to patients with mental disorders. A descriptive study conducted in a Municipal Emergency room in the countryside of the state of São Paulo. We assessed sociodemographic information and about training, attitudes and knowledge on the identification of signs and symptoms, feelings and nursing care for people with mental disorders of 69 nursing technicians. These professionals were characterized as female, adults, with secondary and tertiary educational level. Most received theoretical content on how to identify signs and symptoms, but less than half had received information on the systematization of nursing care (SAE). Despite having much interest in the psychiatry area, the professionals perceived patients with mental disorders as unpredictable individuals in need of constant care. There is need for better investment in issues related to nursing care in order that professionals can offer better quality of care for people with mental disorders.